Perancangan Frontend Pada Sistem Informasi Penerimaan Peserta Didik Baru (PPDB) Di SMK Bina Mandiri Al Qodiriyah Srono - Rusli, Fernica Ernadianis; Hidayat, Alfin; Suardinata, I wayan (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
The use of information technology has become mandatory in various schools in Indonesia, one of which is in the new student admission process (PPDB). However, the new student admission process at SMK Bina Mandiri Al Qodiriyah is still not optimal because it still uses manual procedures and does not have an official web-based system. Therefore, a system is needed to assist the registration and admission process of new students. This research specifically focuses on the interface design stage (frontend/UI/UX) using the Human Centered Design (HCD) approach, without including backend development or database integration. This PPDB information system aims to transform the manual process into an efficient, easily accessible, and enable fast verification of student data. The research produced an interface prototype in the form of a wireframe and mockup that was tested using the usability testing method on 20 respondents (students, parents, and school committee). The results of the usability test showed a user satisfaction level of 85% with an average SUS score of 78, indicating the interface is easy to use and understand. Thus, this design is expected to make a real contribution to schools with limited digital literacy and low internet access.